The Multicultural Education Policies on High School Students in Pattani: A Case Study in Pattani Province, Thailand - Daraha, Kanlaya (Journal of Humanities and Social Sciences Prince of Songkla University, 2017)
A b s t r a c t This research aimed to examine the policy and practices of public high schools in educating culturally diverse students in Pattani. The objectives of the research were; 1) to examine the policies and practices of schools in educating culturally diverse students and 2) to analyze the policies and practices of schools impact based on multicultural framework. Purposive sampling technique was used in this study. The subjects were Buddhist and Muslim students from Benjamarachutit School, Dechapattanayanukul School, and Phokiriratseuksa School. The researcher used qualitative approach. Interviews, observations, and the examination of documents were techniques used for gathering data. The duration of the research started from January 2011 to January 2012. The results revealed that, in general, the policy and practices of the three schools included teaching management, activity management, and school uniform according to students’ culture. These policy and practices satisfied students, parents and communities. Also, the three schools provided courses which matched with students such as Islamic study and Buddhist courses and encuraged the students to live in harmony. บ ท คั ด ย่ อ โครงการวิจัยนี้ได้ศึกษาทำความเข้าใจการจัดการศึกษาในสถานศึกษาของรัฐสำหรับผู้เรียนหลากหลายวัฒนธรรม โดยมีวัตถุประสงค์ของการวิจัยดังนี้ 1) เพื่อศึกษาถึงนโยบายและ การปฏิบัติของสถานศึกษาในการให้การศึกษาแก่ผู้เรียนที่มี ความหลากหลายทางวัฒนธรรม และ 2) เพื่อวิเคราะห์นโยบายและการปฏิบัติของสถานศึกษาตามกรอบแนวคิดพหุวัฒนธรรม โดยเป็นกรณีศึกษาของตัวแทนนักเรียนในจังหวัดชายแดนใต้ คือ จังหวัดปัตตานีซึ่งกลุ่มตัวอย่างที่ใช้ในการศึกษา คือ โรงเรียนมัธยมศึกษาในตัวจังหวัดปัตตานี จำนวน 3 โรงเรียน ได้แก่ โรงเรียนเบญจมราชูทิศ โรงเรียนเดชะปัตตนยานุกูล และโรงเรียนโพธิ์คิรีราชศึกษา ทั้งนี้ สถานศึกษาระดับมัธยมศึกษาที่คัดเลือกมีความแตกต่างด้านนักเรียนที่นับถือศาสนาพุทธและศาสนาอิสลามในสังกัดของสถาบัน ดังนั้น ผู้วิจัยจึงเลือกใช้การวิจัยเชิงคุณภาพ โดยการสัมภาษณ์ การสังเกต และการศึกษาเอกสาร ที่เกี่ยวข้องเป็นกระบวนการในการเก็บรวบรวมข้อมูล การวิจัยครั้งนี้มีระยะเวลาตั้งแต่เดือนมกราคม 2554 - 2555 ในเดือนเดียวกันนี้ ผลการวิจัย พบว่า โรงเรียนที่เป็นกลุ่มตัวอย่างทั้ง 3 โรงเรียน มีนโยบายและการปฏิบัติในเรื่องทั่วไป เช่น นโยบายการจัดการเรียนการสอน การจัดกิจกรรม และการแต่งกายที่ยังคงคำนึง ถึงวัฒนธรรมของผู้เรียน โดยที่นักเรียน และผู้ปกครองมีความ พึงพอใจในนโยบายการศึกษาของสถานศึกษา และพร้อมกันนี้ทางโรงเรียนยังได้มีการส่งเสริมให้นักเรียนอยู่ร่วมกันอย่างสมานฉันท์